MARINASI DAGING SAPI DENGAN MENGGUNAKAN BAWANG PUTIH UNTUK MENINGKATKAN KEAMANAN PANGAN - Nurwantoro Nurwantoro; Yoyok Budi Pramono; Bhakti Etza Setiani; Sigit Sulistiarto; Hermawan Arissaputra; Gilang Ade Perdana; V Priyo Bintoro (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
The research of beef garlic-marinated aims to improve food safety (reducing number of bacteria), to maintain quality of the physical (water holding capacity and cooking loss), to increase of fried-food preference. The study comprised 4 treatments with 5 replicated. T0 : without marination; T1: marination in garlic juice 8 % of beef weight; T2 : marination in garlic crush 8 % of beef weight; T3 : marination in garlic crush 8% + 10% water of beef weight. The result showed that garlic marination gave significant (P<0,05) effect to the total number of bacteria, total coliform bacteria, cooking loss, the aroma and hedonic score. In the other hand, water holding capacity of beef was not significant (P>0,05). The conclussion of the research shows beef garlic-marinated can improve the safety of food, never of physical characteristic and hedonic.